Effect of Leverage, Inventory Intensity, Fixed Asset Intensity, and Political Connections on Tax Aggressiveness (Empirical Study of Multinational Companies Listing on The Indonesia Stock Exchange 2017-2021) - Inggrit Dewi Sartika; Sri Lestari Yuli Prastyatini (Economic and Bussiness Faculty, Dr Soetomo University, 2023)
This study aims to prove empirically thst leverage, inventory intensity, fixed asset intensity, and political connections have an effect on tax aggressiveness. The population of this study are multinational companies listed on the Indonesia Stock Exchange between 2017 and 2021. This survey relied on quantitative research and a variety of secondary data sources. In the population, there are 85 businesses. The sampling technique is 25 companies x 5 years = 125 financial report data from companies. In this case, the analytical method used is multiple linear regression analysis. Testing outcomes of the multiple linear regression coefficients show that Leverage does not affect tax aggressiveness. Inventory intensity influences tax aggressiveness positively. The power of fixed assets has a positive effect on tax aggressiveness. The political connections have no bearing on tax evasion. Keywords: Leverage, inventory intensity, fixed asset intensity, political connections, tax aggressiveness.